4(2-x)=8

4(2-x)=8
2-x =8/4
2-x =2
x =2-2
         therefore x=0

  • 4
Find: 4(2-x)=8
  • -7
4(2-x)=8
4 multiplied 2-x=8
Then 8(4 multiplied by 2)
8-x=8
x=8-8
x=0
  • 0
4[2-x] = 8
8 - 4x = 8
8-8=4x
0=4x
therefore x = 0
  • 1
4(2-x)=8
8-4x=8
-4x=8-8
x=0
   __
   -4
  • -1
-4
  • -6
4(2-x)=8
4x2-4x=8
8-4x=8
-4x=0
X=0x(-4)
X=0
  • -4
4(2-x)=8=4*2=8=8-8=0
  • -4
X=0 as 4(2-x)=8 =4x2=8 so 2-0=2
  • -4
4(2-x)=8
4x2-x=8
8-x=8
-x=8/8=0
As,-x=0 is same as x=0
Hence, x=0

    
  • -3
X-0
  • -2
4( 2- x ) = 8.

Here, 4 is multiplied by ( 2 - x ). 

So, 4( 2-x) = 4*2- 4*x.

=>  8-4x = 8
=> -4x = 8-8 = 0
=> -4x = 0
=> -x = 0/4 = 0.
=> x = 0

Therefore,  x = 0 .
 
  • -3
CDV
 
  • -4
x = 0
  • -4
What are you looking for?